(untitled) (Research, Society and Development, 2024)
Respiratory diseases can affect children, adults and the elderly, consequently they are causes of morbidity and mortality because they represent about 14% of deaths worldwide, as Community Acquired Pneumonia (CAP). Objective: To identify the means of prevention focusing on nursing actions in the prevention, care and care of patients diagnosed with community-acquired bacterial pneumonia. Methodology: presents a Narrative Literature Review, of qualitative nature and descriptive approach. Results: A total of 20 publications were selected from the VHL health platforms, the Research, Society and Development (RSD) and the Scientific Electronic Library Online (SciELO) platform. Results: demonstrated that continuous monitoring is essential for the management of CAP. Final Considerations: The importance of knowing and understanding the nursing diagnoses related to CAP is considered, being fundamental for effective patient care, seeking to prevent complications. In addition, the role of nurses involves health promotion and health education, aiming to improve the quality of life of patients and the general population.